Etika dan Moral dalam Ilmu Pengetahuan - Fatma, Desi; Melisawati, Sri; Renanda, Reni; Ardimen, Ardimen (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
This paper examines Work Ethic Management in Islamic Education. This type of research is a literature study. That is, by examining the concepts of curriculum development and its problems from experts, the author seeks to create an integration of the opinions of these experts. Education is an effort to realize the ideals of the state. But now globalization not only educates people's lives, but has changed the function of education where generations must acquire a variety of knowledge and skills and have morals. Every work without intention is not recognized, because every work that is said to be good deeds is a practice that has sincere intentions. And high job satisfaction is directly related to high motivation as well. Workers are motivated that work is worship and Allah observes everything they do so they strive to achieve excellence, and devote time and energy to work as well as possible. Through this article, the author tries to provide explanations and express verses related to work ethic. The results of this article present the concepts of work ethic management and learning motivation in Islamic education based on the Qur'anic interpretation approach. Keywords: Work Ethic, Learning Motivation, Islamic Education